Knowledge and attitudes toward myopia control strategies among teenagers in Lurambi Constituency, Kenya - Delilah N. Sarai; Alvin J. Munsamy (African Vision and Eye Health)
Background: Myopia is a growing public health issue, particularly among teenagers, due to rapid ocular growth that increases the risk of complications such as retinal detachment and glaucoma. With its global rise, understanding myopia control strategies (MCS) is crucial to reduce prevalence and prevent associated complications.